The pathobiologic spectrum of Schwannomas - (:unkn) unknown (F HERNANDEZ, 2003)
In terms of their morphology, clinical associations and behavior, peripheral nerve sheath tumors are among the most varied of human neoplasm. Not surprisingly, such tumors are subject to frequent misdiagnosis. This is particularly true of the spectrum of schwannomas which include: a) conventional schwannoma, a histologically benign tumor which, on occasion, is destructive of surrounding osseous structures, b) the relatively recently described cellular schwannoma, a tumor that histologically simulates malignant peripheral nerve sheath tumor (MPNST), c) plexiform schwannoma which, particularly in cellular form and when occurring in childhood, simulates MPNST, and d) melanotic schwannoma which is often mistaken for melanoma. The psammomatous form of the latter is often associated with Carney complex, a rare heritable disorder that: a) includes cutaneous lentigines, b) myxomas of skin, subcutaneous tissue, and heart, c) and endocrine neoplasms. The tendency to misdiagnose schwannomas and to overestimate their grade makes schwannomas worthy of note. Herein, we discuss the four major schwannoma variants, their essential clinicopathologic features, and differential diagnosis. The distinction from MPNST is given particular attention.
Keywords: schwannoma; morphology; clinical associations; differential diagnosis; PLEXIFORM MULTINODULAR SCHWANNOMA; NERVE SHEATH TUMOR; MENINGEAL MELANOCYTOMA; CELLULAR SCHWANNOMA; MELANOTIC NEUROFIBROMA; MALIGNANT-MELANOMA; REGULATORY SUBUNIT; CARNEY COMPLEX; GENE; ANGIOSARCOMA